2017
DOI: 10.1017/jmo.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

When and how knowledge sharing benefits team creativity: The importance of cognitive team diversity

Abstract: In this paper, we explored the role of knowledge sharing on team creativity through absorptive capacity and knowledge integration, and tested the condition under which knowledge sharing is positively related to absorptive capacity and knowledge integration. We tested our hypotheses with a sample of 86 knowledge worker teams involving 381 employees and employers in China. Results demonstrate that knowledge sharing was positively related to team creativity, fully mediated by both absorptive capacity and knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 65 publications
3
53
0
1
Order By: Relevance
“…Knowledge sharing is one of the major goals of the organizational knowledge management system through which an organization facilitates the transfer of knowledge among its members (Youssef et al, 2017). Over the past two decades, ample research has identified the positive impact of knowledge sharing on individual, team, and organizational productivity and performance (Dong et al, 2017;Quigley et al, 2007), team creativity and innovation (Cheung et al, 2016;Men et al, 2017), and firm innovation capability (Podrug et al, 2017). However, despite these benefits, organizational efforts to promote knowledge sharing are stalled because of employees' adoption of certain knowledge-hiding behaviors (Černe et al, 2014;Connelly et al, 2012;Lanke, 2018;Škerlavaj et al, 2018;Wang et al, 2018) Knowledge sharing and knowledge hiding seem like two sides of the same coin; however, they are distinct, and consequently, knowledge-sharing practices may not reduce knowledge hiding (Connelly et al, 2012;Connelly and Zweig, 2015).…”
Section: Supervisor Knowledge Hiding From Superviseementioning
confidence: 99%
“…Knowledge sharing is one of the major goals of the organizational knowledge management system through which an organization facilitates the transfer of knowledge among its members (Youssef et al, 2017). Over the past two decades, ample research has identified the positive impact of knowledge sharing on individual, team, and organizational productivity and performance (Dong et al, 2017;Quigley et al, 2007), team creativity and innovation (Cheung et al, 2016;Men et al, 2017), and firm innovation capability (Podrug et al, 2017). However, despite these benefits, organizational efforts to promote knowledge sharing are stalled because of employees' adoption of certain knowledge-hiding behaviors (Černe et al, 2014;Connelly et al, 2012;Lanke, 2018;Škerlavaj et al, 2018;Wang et al, 2018) Knowledge sharing and knowledge hiding seem like two sides of the same coin; however, they are distinct, and consequently, knowledge-sharing practices may not reduce knowledge hiding (Connelly et al, 2012;Connelly and Zweig, 2015).…”
Section: Supervisor Knowledge Hiding From Superviseementioning
confidence: 99%
“…Son et al (2017) also examined the impact of close monitoring on creativity and knowledge sharing and found the mediating role of leader-member exchange. Men et al (2017) investigated when and how knowledge sharing benefitted team creativity, and pointed out the importance of cognitive team diversity.…”
Section: Knowledge Management For Knowledge Sharing and Individual Crmentioning
confidence: 99%
“…Others have categorized diversity at work by surface-level and deep-level diversity, the first representing overt characteristics such as age and gender, while the second represents psychological characteristics such as attitudes, beliefs, and personality (Harrison, Price, & Bell, 1998). Positive impacts on innovation, creativity, and improved productivity have been ascribed to both surface-level and deep-level diversity and particularly to cognitive team diversity (Men, Fong, Luo, Zhong, & Huo, 2017). Such traits may present advantages for employers of those with ASD as their employment may deepen the team’s deep-level diversity and specifically, cognitive team diversity.…”
Section: Literature Reviewmentioning
confidence: 99%